2017
DOI: 10.1186/s40066-017-0106-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of production practices of smallholder potato (Solanum tuberosum L.) farmers in Wolaita zone, southern Ethiopia

Abstract: Background: Potato plays a great role for the achievement of food security program due to its plasticity to environmental conditions and yielding capacity. However, its productivity is far less than other countries due to constraints threatening subsistence farms in Ethiopia. Therefore, potato production practices by smallholder farmers were assessed in Wolaita zone of southern Ethiopia to identify major factors constraining production of the crop. Data were collected at two stages, i.e., at a pilot survey and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 14 publications
4
40
1
Order By: Relevance
“…But these producers were experienced enough to apply some good agricultural practices. These results are not consistent with those of [12] who reported that most (54.2%) of the interviewed households completed primary education in southern Ethiopia, same results were obtained by [13].…”
Section: Discussioncontrasting
confidence: 90%
“…But these producers were experienced enough to apply some good agricultural practices. These results are not consistent with those of [12] who reported that most (54.2%) of the interviewed households completed primary education in southern Ethiopia, same results were obtained by [13].…”
Section: Discussioncontrasting
confidence: 90%
“…This study was conducted in two rural districts (Woredas), namely Humbo and Sodo Zuria in the Wolaita area [25,27]. About 400,000 people live in the districts often suffering from chronic food insecurity problem [5,28]. The households were recruited from lowland (< 1600 m) and midland (> 1600 m) areas.…”
Section: Study Settingmentioning
confidence: 99%
“…Potato ( Solanum tuberosum L.) is a primary non-cereal food crop and ranks 4th in the world because of its high productivity, following corn ( Zea mays L.), rice ( Oryza sativa L.), and wheat ( Triticum aestivum L.) in terms of yield, acreage and value ( 1 ). Potato is considered one of auspicious crop to overcome the challenges of poverty and hunger worldwide ( 2 ).…”
Section: Introductionmentioning
confidence: 99%